2011
DOI: 10.3758/s13423-011-0057-1
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude comparison revisited: An alternative approach to binary choice under uncertainty

Abstract: Two generations of psychologists have been interested in understanding binary choice under uncertainty. In the 1970s and 1980s, researchers assumed that people rely on a two-stage magnitude comparison process to make these decisions (Banks, 1977; Moyer & Dumais, 1978). More recently, the focus has shifted to approaches that rely on probabilistic cues and simple heuristics (Gigerenzer & Goldstein, Psychological Review 103, 650-669, 1996). Here, we test competing predictions derived from these two very different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…Thus, TTB could also predict a distance effect for pairs of recognized objects. In contrast, Brown and Tan (2011) argued that in their study TTB did not predict the observed distance effect, because the pairs that they used could have been answered by considering the same highly valid cue, thus implying no decision-time differences.…”
Section: The Toolbox Approachmentioning
confidence: 86%
See 2 more Smart Citations
“…Thus, TTB could also predict a distance effect for pairs of recognized objects. In contrast, Brown and Tan (2011) argued that in their study TTB did not predict the observed distance effect, because the pairs that they used could have been answered by considering the same highly valid cue, thus implying no decision-time differences.…”
Section: The Toolbox Approachmentioning
confidence: 86%
“…As an alternative, Brown and Tan (2011) recently proposed that participants may engage in magnitude comparisons that are based on subjectively built orders of the objects involved. They tested a set of 16 cars (asking for the more expensive one in each pair) and found that participants' decision times were better explained by assuming magnitude comparisons based on subjective linear orders than by assuming the use of specific heuristics, as predicted by the toolbox approach.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the overlap between this new line of research and the symbolic comparison literature from the 1970s and 1980s, both proponents and critics of fast-and-frugal inference heuristics have neglected this earlier research and have come to conceptualize the judgment process (and the underlying processing architecture) in a fundamentally different way (Brown & Tan, 2011). We next describe the different process models for choice situations involving one recognized and one unrecognized object.…”
Section: Comparative Magnitude Judgments and The Distance Effectmentioning
confidence: 99%
“…SDEs have been documented in a wide variety of knowledge domains, which include (a) comparisons on concrete dimensions such as the sizes of animals (e.g., Moyer, 1973) and other everyday objects (Paivio, 1975); (b) comparisons on abstract dimensions such as the magnitudes of numbers (e.g., Dehaene, Dupoux, & Mehler, 1990;Moyer & Landauer, 1967), time, quality, temperature terms (Holyoak & Walker, 1976), and the semantic goodness of words (A. Friedman, 1978); and (c) comparisons that involve some degree of uncertainty with respect to the position of target items along the criterion dimension, such as the military power of countries (Kerst & Howard, 1977) and the price of cars (Brown & Tan, 2011).…”
Section: Comparative Magnitude Judgments and The Distance Effectmentioning
confidence: 99%